Assessing the efficiency of Turkish secondary education: Heterogeneity, centralization, and scale diseconomies - (:unkn) unknown (My University, 2010)
This paper begins with a historical overview of the Turkish educational system. We then use Data Envelopment Analysis (DEA) and econometric methods to evaluate the system's efficiency. In doing so we identify scale diseconomies and relate them to underlying structural characteristics of the system. Selected suggestions on improving performance are offered. The roles of heterogeneity and centralization are also highlighted. Heterogeneity is modeled as an undesirable measure. The linkage between indicators of centralization and scale diseconomies was found to be statistically significant. The authors believe this to be the first study that investigates the impact of systemic characteristics such as heterogeneity and centralized structure on educational outcomes for Turkey. Since the country straddles the Middle East and the Balkans, culturally as well as geographically, it may be of interest to other countries in the region. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Data Envelopment Analysis (DEA); Decentralization; Decision rights; Decreasing returns to scale (DRS); Directional distance function; Undesirable outputs